The Effectiveness of Using the Alef Education Platform in English Language Learning at Madrasah Aliyah Ar Rosyaad Kediri - Arwan Rifa'i (Essence: Journal of English Language Teaching, Linguistics, and Literature, 2025)
This study examines the effectiveness of using the Alef platform in English language learning at Madrasah Aliyah Ar Rosyaad Kediri. The research aims to evaluate the impact of implementing this digital platform on the process and outcomes of English language learning. A mixed-method research approach was employed, with data collected through classroom observations, interviews with teachers and students, and English proficiency tests conducted before and after the implementation of the Alef platform. The findings indicate a significant improvement in students' learning motivation, vocabulary mastery, and English communication skills. The Alef platform proved effective in creating an interactive learning environment that facilitates both independent and collaborative learning. Although some technical challenges were encountered during implementation, the pedagogical benefits outweighed the obstacles faced. This study concludes that integrating the Alef platform into English language learning at Madrasah Aliyah Ar Rosyaad Kediri positively contributes to enhancing the quality of instruction and improving student learning outcomes.